2014
DOI: 10.3892/ijmm.2014.1948
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of TRAF4 expression suppresses osteosarcoma cell growth in vitro and in vivo

Abstract: Tumor necrosis factor (TNF) receptor-associated factor 4 (TRAF4) is an adapter molecule that is overexpressed in certain cancers. TRAF4 is overexpressed in osteosarcoma tissues and osteosarcoma cells. Using the technique of RNA interference, the expression of TRAF4 in the human osteosarcoma Saos-2 cell line was shown to be downregulated. The proliferation, cell cycle arrest and apoptosis ability of Saos‑2 cells were examined, as was tumor development in a xenograft mouse model. The results showed that the TRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
0
1
Order By: Relevance
“…DLEU1 is positively associated with TRAF4. TraF4 serves an important role in other cancers according to previous studies (25)(26)(27)(28). Querying GePia revealed that the expression of TraF4 in the dleu1-mirna-demrna network was positively associated with dleu1 ( Fig.…”
Section: Go and Pathway Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…DLEU1 is positively associated with TRAF4. TraF4 serves an important role in other cancers according to previous studies (25)(26)(27)(28). Querying GePia revealed that the expression of TraF4 in the dleu1-mirna-demrna network was positively associated with dleu1 ( Fig.…”
Section: Go and Pathway Analysissupporting
confidence: 58%
“…TraF4 is overexpressed in tissues or cells in osteosarcoma (25), colon cancer (26), oral squamous cell carcinoma (27) and breast cancer (28). Presently, the knockdown of TraF4 inhibited cell proliferation, migration and invasion, and induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…TRAF4 is overexpressed in certain cancers, such as osteosarcoma cells, and regulated osteosarcoma cell growth (Yao et al . ). The RAB34 ‐encoded protein is a member of the RAB family of proteins, which is a Golgi‐bound member of the secretory pathway that is involved in the repositioning of lysosomes and the activation of macropinocytosis.…”
Section: Discussionmentioning
confidence: 97%
“…TRAF6 regulates the proliferation, apoptosis and invasion of OSA cells ( 30 ). The knockdown of TRAF4 expression suppresses OSA cell growth in vitro and in vivo ( 31 ). The study by Yao et al indicated that TRAF4 can also enhance OSA cell invasion through the AKT signaling pathway ( 32 ).…”
Section: Discussionmentioning
confidence: 99%